Truncated-exponential-based Frobenius–Euler polynomials - Kumam, Wiyada; Srivastava, Hari M.; Wani, Shahid Ahmad; Wani, Shahid Ahmad; Araci, Serkan; Kumam, Poom; Aracı, Serkan (Springer, 2019)
In this paper, we first introduce a new family of polynomials, which are called the truncated-exponential based Frobenius–Euler polynomials, based upon an exponential generating function. By making use of this exponential generating function, we obtain their several new properties and explicit summation formulas. Finally, we consider the truncated-exponential based Apostol-type Frobenius–Euler polynomials and their quasi-monomial properties.
Keywords: Frobenius–Euler polynomials; Monomiality principle; Quasi-monmiality principle; Summation formulas; Truncated-exponential based polynomials